A review of the role of pollination on the yield of cocoa plant - Dani Dani; Dewi Nur Rokhmah (Universitas Padjadjaran, 2022)
AbstractYield of cocoa (Theobroma cacao L.) plant, in form of cocoa seeds, is produced through the process of sexual reproduction. Pollination plays an important role in the successful formation of cocoa fruit and seeds. In addition, number of ovules per ovary, degree of self-incompatibility, and xenia effect are also affected the final yield. Those characters are determined by genetic factors. Cocoa flowers that are not pollinated fall within 24 hours and fail to develop into fruits and seeds. Pollination intensity up to a certain level showed a significant effect on increasing the percentage of fruit formation and the number of seeds per fruit. The role of pollinating insects, especially from the Ceratopogonidae family, is very important in dispersing pollen grains, allowing the natural pollination process to be occurred.Keywords: fertilization, xenia, meta-xenia, pollinator. AbstrakHasil tanaman kakao (Theobroma cacao L.) adalah berupa biji yang dihasilkan melalui proses reproduksi seksual. Polinasi memegang peranan penting dalam keberhasilan pembentukan buah dan biji tanaman kakao. Selain itu, hasil akhir tanaman kakao juga dipengaruhi oleh karakter jumlah ovul per ovarium, tingkat inkompatibilitas sendiri, dan efek xenia. Karakter-karakter tersebut dikendalikan secara genetik. Bunga kakao yang tidak diserbuki akan gugur dalam waktu 24 jam dan gagal berkembang menjadi buah dan biji. Intensitas polinasi hingga level tertentu menunjukkan pengaruh yang nyata terhadap peningkatan persentase pembentukan buah dan jumlah biji per buah. Peran serangga penyerbuk, terutama dari famili Ceratopogonidae, sangat penting dalam menyebarkan polen sehingga proses polinasi secara alami dapat terjadi.Kata Kunci: pembuahan, xenia, meta-xenia, polinator